Keanekaragaman Serangga pada Tanaman Tomat (Lycopersicum esculentum Mill.) di Desa Ogomolos - Dirham Dirham; Carolus Noprianto; Manap Trianto (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
This study aims to determine the diversity of insects found in tomato plants (Lycoperscium escelentum Mill.). This research was conducted on tomato farming land in the village of Ogomolos, Mepanga District, Central Sulawesi from February to March 2018. This type of research in descriptive qualitative with a sampling technique using survey methods. This study use three insect trapping techniques (Sweep net, Pitfall trap and Yellos sticky trap). Based on the result of the research that has been carried out, the results obtained are 658 individuals consisting of 18 types of nsects from 9 orders and 16 families. The value of the insect diversity index of Shannor-Weiner (H’) = 2,282 is classified as moderate.